Comparison of Surgical Outcome Between Quickert Suture and Quickert Suture With Modified Lateral Tarsal Strip in Involutional Lower Eyelid Entropion. Issue 1 (January 2016) - Baek, Ji Sun; Choi, Seong Chan; Jang, Sun Young; Lee, Jung Hye; Choi, Hye Sun
Abstract : Purpose: To evaluate the surgical outcome between Quickert suture and Quickert suture with modified lateral tarsal strip in involutional lower eyelid entropion. Methods: A retrospective study was performed on 76 patients (94 eyes) who had undergone Quickert suture (Group 1) and on 38 patients (44 eyes) who had undergone Quickert suture with modified lateral tarsal strip (Group 2) for correction of involutional lower eyelid entropion from January 2011 to December 2013. Results: In Group 1, recurrence rate is 25.5% (24 eyes) and mean duration to recurrence is 11.9 months in Group 1. For correction of recurrence, Quickert suture is performed in 50% (12 eyes), Quickert suture with lateral tarsal strip is performed in 37.5% (9 eyes), and lateral tarsal strip is performed in 12.5% (3 eyes). In Group 2, recurrence rate is 9.1% (4 eyes). For correction of recurrence, lower eyelid retractor reinsertion is performed in 50% (2 eyes), Quickert suture with lateral tarsal strip is performed in 25% (1 eye), and Quickert suture is performed in 25% (1 eye). Conclusions: Recurrence rate is lower in patients who had undergone Quickert suture with modified lateral tarsal strip than in a patient who had undergone Quickert suture for correction of involutional lower eyelid entropion.